Evaluation of the Effectiveness of Digital Teaching Materials on Google Sites-Based "Relationships and Functions" Materials: Accessibility Analysis and User Feedback - APRILIANI, MALA; PRAMUDITYA, SURYA AMAMI (Journal Of Education, 2025)
This research is motivated by the importance of evaluating digital learning materials to ensure their quality and effectiveness in learning. The objective was to evaluate the effectiveness of the Google Sites-based digital learning material "Relations and Functions" through accessibility analysis and user feedback. The method used was descriptive quantitative, with data collected using an online Likert-scale questionnaire from two peer teachers (accessibility test) and one teacher and several students (feedback test). The main results showed that the technical aspects and learning feasibility received excellent ratings (100% each) in the accessibility test, while visual design (88.9%) and interactivity (77.8%) still needed improvement. On the other hand, user feedback showed lower scores in the technical (61.4%), pedagogical (64.74%), and aesthetic (65.74%) dimensions. The implication is that although it meets basic standards, this learning material requires further optimization, especially in interactivity, responsiveness, and visual design, to improve the overall learning experience and user engagement.